Formulation and characterization of bilayer films based on Brea gum and Pectin - Slavutsky, Anibal Marcelo (2018)
The formulation of bilayer films is a strategy aimed at combining the advantages and properties of different film-forming materials. Bilayer films based on pectin and brea gum were formulated and their functional properties studied and compared with those presented by single layer films of each component. The micrographs and surface properties confirmed that the bilayer films can maintain their identity and prevent delamination. The mechanical properties of the films depended on the characteristics of the polymers and their interactions, and the bilayer films showed prevalence of the brea gum properties. The brea gum films showed high solubility that influenced the bilayer film solubility. The water vapour permeability of the bilayer films was dependent on the material that was exposed to the side where desorption occurred. The bilayer films presented lower water vapour permeability than the brea gum films but higher than that of pectin films of similar thicknesses. The differential properties of each layer of bilayer films make them potentially interesting for controlled drug release.